2013
DOI: 10.14295/rbho.v19i2.655
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da viabilidade de sementes de brassavola tuberculata hook. em função do período de armazenamento, tempo de cultivo e tratamento pré-germinativo

Abstract: <p>A germinação assimbiótica é um dos principais métodos de multiplicação de Orchidaceae. Entretanto, a viabilidade das sementes dessa família botânica é susceptível a fatores bióticos e abióticos que podem inviabilizar esse processo. Objetivouse com este trabalho avaliar o efeito do período de armazenamento, de tratamento pré-germinativo e do tempo de cultivo sobre a porcentagem de germinação das sementes de <em>Brassavola tuberculata </em>e também verificar se o procedimento amostral do tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…When studying the viability of Brassavola tuberculata Hook. seeds, Rosa et al (2013) reported a low correlation of the tetrazolium test results with the germination percentage, inferring that the sample method of this test can only be used to predict seed viability and not the likely germination percentage. These results refer to the mode of action of the test, which reflects the activity of the dehydrogenase enzymes involved in the respiration process, making it possible to distinguish the living parts of the seeds from the dead ones, which do not change color (Oliveira et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying the viability of Brassavola tuberculata Hook. seeds, Rosa et al (2013) reported a low correlation of the tetrazolium test results with the germination percentage, inferring that the sample method of this test can only be used to predict seed viability and not the likely germination percentage. These results refer to the mode of action of the test, which reflects the activity of the dehydrogenase enzymes involved in the respiration process, making it possible to distinguish the living parts of the seeds from the dead ones, which do not change color (Oliveira et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…After manual shaking, the propagules suspension was poured into a Petri dish and the total number of seeds and the number of germinated seedlings were counted using a binocular stereoscopic zoom microscope. The germination percentage was calculated using the following formula (Rosa et al 2013): (number of geminated seedlings x 100)/total number of observed seeds.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we used a binocular stereoscopic microscope to count non germinated seeds (NS) and chlorophyll propagules (CP). We calculated germination percentage (G%) according to modified ROSA et al (2013), using the following expression:…”
Section: Methodsmentioning
confidence: 99%
“…Cinco frutos foram colhidos aos 210 dias após sua formação (Rosa et al 2013, Macedo et al 2014 e levados para o Laboratório de Cultivo in vitro, onde foram lavados com água corrente e, na sequência, alocados em Béquer com capacidade para 500 mL e desinfestados com 300 mL de álcool (70%) por cinco minutos, para minimizar a possível contaminação. A seguir, os frutos desinfestados foram abertos com auxílio de bisturi e as sementes foram removidas e homogeneizadas.…”
Section: Methodsunclassified